2023
DOI: 10.1002/pol.20230026
|View full text |Cite
|
Sign up to set email alerts
|

Lignin‐based covalent adaptable network resins for digital light projection 3D printing

Abstract: Abstract3D printing is a low cost, customizable, and fast‐growing technology with the potential to revolutionize plastic manufacturing. Vat photopolymerization 3D printing technologies stand out for their high resolution, however, the resulting printed materials are made from petroleum feedstocks and are covalently crosslinked which renders them unrecyclable. Here, resin formulations with 70 wt% bio‐based content and dynamic functionality are synthesized and printed using lignin, vanillin, and soybean oil comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Annealing dramatically increased the Young's modulus and UTS, providing these thermosets with superior mechanical perfrormance to previously reported bio-based materials. 33,34 Further optimization of the reprocessing parameters is to be explored to quantify the reprocessability of the three thermoset formulations. Additionally, the abundance of ester moieties could allow exploration of chemical degradability to strive for full recyclability through chemical recycling.…”
Section: Polymer Chemistry Papermentioning
confidence: 99%
See 2 more Smart Citations
“…Annealing dramatically increased the Young's modulus and UTS, providing these thermosets with superior mechanical perfrormance to previously reported bio-based materials. 33,34 Further optimization of the reprocessing parameters is to be explored to quantify the reprocessability of the three thermoset formulations. Additionally, the abundance of ester moieties could allow exploration of chemical degradability to strive for full recyclability through chemical recycling.…”
Section: Polymer Chemistry Papermentioning
confidence: 99%
“…Transesterification reactions are very commonly used for designing VP printable vitrimers, 27,[30][31][32] and although more common in recent years, the reports that additionally take advantage of using bio-based feedstocks remain limited. Fei et al 33,34 reported a DLP printable resin formulation with ∼62.5 to 68 wt% bio-based content from dimer acid. These materials showed self-healing and reprocessability due to dynamic transesterification reactions, and reported healing efficiencies of maximum 65%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To render the canonic thermosets more sustainable, considerable efforts have been dedicated toward designing bio-based CANs from renewable resources, especially in the past decade. The targeted feedstocks are vegetable oils, , natural rubbers, sugars, lignin, , and lignin derivatives. , The increasing interest into the advanced CAN materials is evidenced by several excellent reviews on the topic, ,,, while the number of publications involving CANs has also raised significantly, especially in the past few years. Considering the period from 2009 to 2023 (updated on April 2023), 538 results were generated on Web of Science using the keyword “covalent adaptable networks” (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Designing the starting material appropriately is not straightforward as the addition of lignin affects various conditions in 3D printing, such as melt rheology in FFF, viscoelasticity in DIW, or light-curing ability in SLA . Furthermore, when used as a pure filler, lignin typically weakens the overall performance of the final material, necessitating chemical modification for proper dispersion within the polymer matrix. , This issue is especially pronounced in vat photopolymer 3D printing, including SLA and related technologies, as unmodified lignin struggles to achieve homogeneous dispersion and solubility in liquid epoxy- or (meth)­acrylate-based resins. This leads to phase separation or sedimentation during printing, resulting in structural inhomogeneity in the final material.…”
Section: Introductionmentioning
confidence: 99%